2016
DOI: 10.1242/dev.139238
|View full text |Cite
|
Sign up to set email alerts
|

TAEL: A zebrafish-optimized optogenetic gene expression system with fine spatial and temporal control

Abstract: Here, we describe an optogenetic gene expression system optimized for use in zebrafish. This system overcomes the limitations of current inducible expression systems by enabling robust spatial and temporal regulation of gene expression in living organisms. Because existing optogenetic systems show toxicity in zebrafish, we re-engineered the blue-light-activated EL222 system for minimal toxicity while exhibiting a large range of induction, fine spatial precision and rapid kinetics. We validate several strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 54 publications
4
91
0
Order By: Relevance
“…They will allow us to ask questions originally answered through classical explant‐based methods, but with much more precision. Zebrafish is leading the way in development and application of photoactivatable tools with which to dissect roles of major signaling pathways . The resulting data sets will be complex and computational approaches will be necessary for their analysis, as well as for generating predictions to test in further experiments .…”
Section: Dorsoventral Pattern In the Forebrain Primordiummentioning
confidence: 99%
See 1 more Smart Citation
“…They will allow us to ask questions originally answered through classical explant‐based methods, but with much more precision. Zebrafish is leading the way in development and application of photoactivatable tools with which to dissect roles of major signaling pathways . The resulting data sets will be complex and computational approaches will be necessary for their analysis, as well as for generating predictions to test in further experiments .…”
Section: Dorsoventral Pattern In the Forebrain Primordiummentioning
confidence: 99%
“…Zebrafish is leading the way in development and application of photoactivatable tools with which to dissect roles of major signaling pathways. [61][62][63][64][65] The resulting data sets will be complex and computational approaches will be necessary for their analysis, as well as for generating predictions to test in further experiments. 19,20 The power and feasibility of this approach have been demonstrated in recent studies in zebrafish.…”
Section: Dorsoventral Pattern In the Forebrain Primordiummentioning
confidence: 99%
“…4d) 35,41-46 . In addition, the LOV domain-containing transcription factor EL222 has been fused with heterologous activation domains to achieve light-dependent gene expression in zebrafish embryos 47,48 . This bacterial photoreceptor is composed of LOV and DNA-binding domains that are connected through a regulatory Jα helix, and the monomeric dark state is sterically occluded from complexing DNA.…”
Section: Photoactivatable Probes Of Gene Functionmentioning
confidence: 99%
“…Blue-light illumination leads to Jα helix unfolding, allowing EL222 to form a transcriptionally active homodimer, and thermal reversion follows within seconds. Such optogenetic tools have been used to compare the effects of sustained and oscillatory Notch pathway activation in cultured murine neural progenitors and to induce endodermal cell fates in zebrafish embryos 48,49 .…”
Section: Photoactivatable Probes Of Gene Functionmentioning
confidence: 99%
“…The authors were able to use the system, named TAEL, to induce ectopic endodermal cells in the presumptive ectoderm via targeted induction of the transcription factor sox32 and modulation of Nodal signaling dynamics by inducing lefty1 expression. Furthermore, the authors demonstrated how their LOV-based system can be used together with the latest genome-editing technology, CRISPR/Cas9, to induce gene mutations specifically in cells irradiated by light 126 ( Figure 3C). …”
Section: Emerging Optogenetic Technologiesmentioning
confidence: 99%